MEASUREMENT OF LASER BEAM PROFILE AFTER PROPAGATION THROUGH UNTWISTED AND TWISTED SILICA MICROSTRUCTURED OPTICAL FIBERS WITH A HOLLOW RING CORE DOPED WITH GeO₂ (Eureka Journal of Computing Science & Digital Innovation, 2026)
This paper presents the results of laser beam profile measurements previously performed on a designed and successfully fabricated silica microstructured optical fiber (MOF) featuring a hollow ring core (HRC) doped with GeO₂. We present selected results of laser beam profile measurements—conducted under various launch conditions (utilizing different laser sources as well as different excitation fibers, specifically a commercially available ITU-T Rec. G.652 single-mode fiber and a 50/125 ISO/IEC Cat. OM2+/OM3 multimode fiber)—at the output ends of the investigated MOF-HRC samples (both untwisted and twisted), as well as at the output end of a large-core 100/125 multimode fiber excited by the MOF-HRC.
Keywords: Hollow-core silicon microstructured optical fiber, twisted silicon microstructured optical fiber, laser beam profile, hollow annular cores.